Shifting Perspectives in Adaptations - Bálint, Emma (Hungarian Journal of English and American Studies, 2020)
Book review:Grossman, Julie. Literature, Film, and Their Hideous Progeny: Adaptation and ElasTEXTity. Adaptation and Visual Culture 1. London: Palgrave Macmillan, 2015. 228 pages. ISBN 978-1-137-54205-4. Hb. $99.00.